2018
DOI: 10.1200/jgo.2016.008714
|View full text |Cite
|
Sign up to set email alerts
|

Building a Network of Health Professionals for Breast and Cervical Cancer Control in the Andean Region

Abstract: PurposeCancer mortality is approximately twice as high in Latin American countries than in more developed countries. In particular, the countries of the high Andean region of Latin America carry a double burden of breast and cervical cancers. In these countries, there are disproportionately higher mortality to incidence ratios compared with other regions in Latin America. The US National Cancer Institute’s Center for Global Health, the Pan American Health Organization, and the Ministry of Health in Peru collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Its main objective was to increase access to cancer care services. To accomplish this goal, the policy was accompanied by an investment of $290 million [ 18 ]. With that funding, Plan Esperanza expanded access to care for low-income individuals by providing free cancer care coverage to individuals with SIS [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its main objective was to increase access to cancer care services. To accomplish this goal, the policy was accompanied by an investment of $290 million [ 18 ]. With that funding, Plan Esperanza expanded access to care for low-income individuals by providing free cancer care coverage to individuals with SIS [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This literature review indicates the gap between policy and implementation is due, in part, to insufficient organizational competencies to implement models of care delivery that shift care from the hospital to the community, unequal distribution of health infrastructure and health care workforce [ 1 2 11 18 29 30 32 ], and differences in access to health insurance [ 38 ]. The centralization of resources to Lima continues to limit the ability of providers to a) implement national plans and b) diagnose and treat cervical cancer outside of the capital city [ 1 2 11 18 29 30 32 ]. In addition, the government has limited capability to conduct system evaluations of the effectiveness of new delivery approaches, which hinders country-level evidence generation [ 17 33 34 ].…”
Section: Policy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ overall positive attitudes towards the program are in line with prior programs establishing knowledge-sharing collaboratives. Such programs have similarly found that these workshops and programs offer participants an opportunity to discuss key issues surrounding their target disease with regional and international experts across a large swath of topics ( 20 ). Both HICs and LMICs benefit from knowledge sharing relationships, though prior research has emphasized that their topic interests and needs differ and that this is an important consideration ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from each region were described previously 12 . For the current study, we identified common themes expressed in the narratives across the 3 regions.…”
Section: Methodsmentioning
confidence: 99%